A toxic shrub turned therapeutic: The dichotomy of Nerium oleander bioactivities. (1st March 2023) - Sharma, Rajat; Singh, Swati; Tewari, Nisha; Dey, Priyankar
Abstract: Nerium oleander L. is a medicinal plant, used for the treatment of cancers and hyperglycemia across the world, especially in Indian sub-continent, Turkey, Morocco, and China. Although clinical studies supporting its pharmacological effects remain critically underexplored, accidental and intentional consumption of any part of the plant causes fatal toxicity in animals and humans. While the polyphenolic fraction of oleander leaves has been attributed to its pre-clinical pharmacological activities, the presence of diverse cardiac glycosides (especially oleandrin) causes apoptosis to cancer cells in vitro and results in clinical signs of oleander poisoning. Thus, the dual pharmacological and toxicological role of oleander is a perplexing dichotomy in phytotherapy. The current investigative review, therefore, intended to analyze the intrinsic and extrinsic factors that likely contribute to this conundrum. Especially by focusing on gut microbial diversity, abundance, and metabolic functions, oleander-associated pharmacological and toxicological studies have been critically analyzed to define the dual effects of oleander. Electronic databases were extensively screened for relevant research articles (including pre-clinical and clinical) related to oleander bioactivities and toxicity. Taxonomic preference was given to the plant N. oleander L. and synonymous plants as per 'The World Flora Online' database (WCSP record #135196). Discussion on yellow oleander ( Cascabela thevetia (L.) Lippold) has intentionally been avoided since it is a different plant. The review indicates that the gut microbiota likely plays a key role in differentially modulating the pharmacological and toxicological effects of oleander. Other factors identified influencing the oleander bioactivities include dose and mode of treatment, cardiac glycoside pharmacokinetics, host-endogenous glycosides, plant material processing and phytochemical extraction methods, plant genotypic variations, environmental effects on the phytochemical quality and quantity, gene expression variations, host dietary patterns and co-morbidity, etc. The arguments proposed are also relevant to other medicinal plants containing toxic cardiac glycosides. Graphical abstract: Image 1 Highlights: Oleander demonstrate both pharmacological and toxicological properties. Gut microbiota differentially metabolize polyphenolics and toxic cardenolides. Reduced oleander toxicity may result due to specific gut microbes. Extrinsic and intrinsic factors affect bioavailability and bioactivity. Gut microbiota may also dictate metabolic health benefits of oleander.